Do You See What I See? Effectiveness of 360-Degree vs. 2D Video Ads Using a Neuroscience Approach - Ausin-Azofra, Jose M.; Bigne, Enrique; Ruiz, Carla; Marín-Morales, Javier; Guixeres, Jaime; Alcañiz, Mariano (Frontiers in Psychology, 2021)
This study compares cognitive and emotional responses to 360-degree versus static (2D) videos in terms of visual attention, brand recognition, engagement, and emotions. Hypotheses are proposed based on the interactivity literature, cognitive overload, advertising response model and motivation, opportunity, and ability theoretical frameworks, and tested using neurophysiological tools: electroencephalography, eye-tracking, electrodermal activity, and facial coding. In testing four existing ads for durable goods and fast-moving consumer goods (FMCG) this research explains the mechanism through which 360-degree video ads outperform standard versions. The results revealed that gaze view depends on ad content, visual attention paid being lower in 360-degree FMCG ads than in 2D ads. Brand logo recognition is lower in 360-degree ads than in 2D video ads. Overall, 360-degree videos for durable products increase positive emotions and viewer engagement with the ads, which carries the risk of non-exposure to some of the ad content.